2020
DOI: 10.1101/2020.11.09.20228494
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in sexual behavior, PrEP adherence, and access to sexual health services due to the COVID-19 pandemic among a cohort of PrEP-using MSM in the South

Abstract: BackgroundThe COVID-19 pandemic has had unforeseen consequences on the delivery of HIV and STD prevention services. However, little is known about how the pandemic has impacted PrEP-using men who have sex with men (MSM).MethodsData come from an online cohort of PrEP-using MSM in the Southern United States from October 2019 to July 2020. Participants were administered ten surveys in total, including one ad hoc survey specifically on COVID-19. We conducted a cross-sectional analysis of this ad hoc survey (n=56) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 9 publications
2
45
0
Order By: Relevance
“…Empirical data suggests a wide heterogeneity of changes in sexual activity during initial COVID-19 restrictions in March 2020 [ 7 , 8 ]. However, fewer studies have characterized the timing of behavioral rebounds; some have suggested a return to pre–COVID-19 levels starting as early as June 2020 [ 9 , 10 ]. Our model suggests that such a transient change will have no substantive impact for HIV and only a minor impact for STIs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Empirical data suggests a wide heterogeneity of changes in sexual activity during initial COVID-19 restrictions in March 2020 [ 7 , 8 ]. However, fewer studies have characterized the timing of behavioral rebounds; some have suggested a return to pre–COVID-19 levels starting as early as June 2020 [ 9 , 10 ]. Our model suggests that such a transient change will have no substantive impact for HIV and only a minor impact for STIs.…”
Section: Discussionmentioning
confidence: 99%
“…These were reduced on a relative scale individually and jointly. We selected the joint 50% relative reduction in sexual behavior and clinical services as a key scenario to highlight in figures based on empirical data suggesting upwards of this level of change [ 7 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, COVID-19 was quickly spreading across the globe leaving horrific rates of illness, hospitalizations, and death in its wake. To protect patients and staff, some HIV and sexual health clinics limited business operations or provided services only virtually [ 4 , 5 ]. In essence, they opted for a population-level quarantine—effectively waving the black flag by selecting this blunt yet powerful tool [ 4 , 5 ].…”
mentioning
confidence: 99%